Embedding Reading Skills and Value Education Within Structural Scaffolding: Analyzing Novice Arabic Texts in the Digital Age - Ammar Zainuddin; Muqimah Liwais Sunnah; Ninik Indrawati (Al-Muyassar: Journal of Arabic Education, 2026)
Basic level Arabic language learning is often reduced to mere phonetic exercises, separating linguistic mastery from value education. However, integrating character education in contemporary Arabic pedagogy is highly urgent, as novice learners in the digital age face moral and ecological crises demanding holistic interventions from an early age. This study aims to explore the anatomy of structural scaffolding and the core moral values embedded in novice-level (mubtadi) reading texts on the 3asafeer digital platform. Utilizing Krippendorff's Qualitative Content Analysis, 12 texts were purposively sampled based on novice-level classifications (Levels Jim to Waw) and genre diversity. The results revealed two main findings. First, strict word quantity limitation (1-15 words per page) and engineered syntactic progression act as cognitive scaffolding to manage visual attention and facilitate reading skills—a practical strategy educators can directly implement for material design. Second, through this syntactic simplification, the texts brilliantly embed four 21st-century values via relatable daily contexts: mental resilience (e.g., reframing failure), ecological literacy (e.g., observing nature's patterns), global awareness (e.g., redefining everyday heroism), and digital wellbeing (e.g., managing screen time). This research concludes that grammatical limitation is not a weakness, but a powerful hidden curriculum instrument, offering curriculum developers and textbook authors a practical blueprint to simultaneously embed value education into the development of reading skills and children's moral maturity.